If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -10x = 48 + -17x Solving 12 + -10x = 48 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. 12 + -10x + 17x = 48 + -17x + 17x Combine like terms: -10x + 17x = 7x 12 + 7x = 48 + -17x + 17x Combine like terms: -17x + 17x = 0 12 + 7x = 48 + 0 12 + 7x = 48 Add '-12' to each side of the equation. 12 + -12 + 7x = 48 + -12 Combine like terms: 12 + -12 = 0 0 + 7x = 48 + -12 7x = 48 + -12 Combine like terms: 48 + -12 = 36 7x = 36 Divide each side by '7'. x = 5.142857143 Simplifying x = 5.142857143
| 137-4x=32x+17 | | 2m+15=3m+12 | | 6x-3=1+4x | | (9xY)+15=(14xY) | | 4x^2-24x+17=0 | | 0=x^2+7x+14 | | 9+5x=-3x-79 | | 3(x+3)=2x+30 | | 0=x^2+7+14 | | 6(x-2)=3(x+1) | | 6(x-2)=3(x+1) | | 10=b(2+3) | | 8b+2b= | | 7x+2y=14 | | 6x+6=-124-7x | | 6x+7=34+3x | | 5x+31=12x-53 | | 82-3x=2x+17 | | 234-4x=32x+22 | | 7-7x=152-42x | | 4x-9=-3x-93 | | -2x-7=-11-x | | 6y^2-9y=1 | | 3x-2=-6+5x | | 8n=6n-11n | | 8x+16=5x+16 | | 2x+(3x-3)=103 | | 79-7x=38x+19 | | -7x+6=6+6x | | 12-z=16-3z | | 4x+31=11x-39 | | 2x+-3=103 |